Harnessing plant growth-promoting rhizobacteria, Bacillus subtilis and B. aryabhattai to combat salt stress in rice: a study on the regulation of antioxidant defense, ion homeostasis, and photosynthetic parameters - Siddika, Ayesha; Rashid, Alfi Anjum; Khan, Shakila Nargis; Khatun, Amena; Karim, Muhammad Manjurul; Prasad, P.V. Vara; Hasanuzzaman, Mirza (Frontiers in Plant Science, 2024)
The ongoing global expansion of salt-affected land is a significant factor, limiting the growth and yield of crops, particularly rice (Oryza sativa L). This experiment explores the mitigation of salt-induced damage in rice (cv BRRI dhan100) following the application of plant growth-promoting rhizobacteria (PGPR). Rice seedlings, at five- and six-weeks post-transplanting, were subjected to salt stress treatments using 50 and 100 mM NaCl at seven-day intervals. Bacterial cultures consisting of endophytic PGPR (Bacillus subtilis and B. aryabhattai) and an epiphytic PGPR (B. aryabhattai) were administered at three critical stages: transplantation of 42-day-old seedlings, vegetative stage at five weeks post-transplantation, and panicle initiation stage at seven weeks post-transplantation. Salt stress induced osmotic stress, ionic imbalances, and oxidative damage in rice plants, with consequent negative effects on growth, decrease in photosynthetic efficiency, and changes in hormonal regulation, along with increased methylglyoxal (MG) toxicity. PGPR treatment alleviated salinity effects by improving plant antioxidant defenses, restoring ionic equilibrium, enhancing water balance, increasing nutrient uptake, improving photosynthetic attributes, bolstering hormone synthesis, and enhancing MG detoxification. These findings highlight the potential of PGPR to bolster physiological and biochemical functionality in rice by serving as an effective buffer against salt stress–induced damage. B. subtilis showed the greatest benefits, while both the endophytic and epiphytic B. aryabhattai had commendable effects in mitigating salt stress–induced damage in rice plants.